Petrogenesis, tectonic setting and geodynamic implications of keziergayin granites in the kelan basin (Chinese Altai): constraints from geochemistry, zircon U-Pb geochronology and Nd‒Hf‒Pb‒O isotopes - Weng, Kai; Kang, Wenbin; Zhao, Xiaojian; Ma, Zhongping; Cao, Jifei; Sui, Qinglin (Frontiers in Earth Science, 2023)
The Chinese Altai is characterized by abundant granitoids, which not only are indicators of the interaction between crust and mantle but also provide critical constraints on the tectonic evolution of the orogen. This study presents zircon U‒Pb‒O isotopes, whole-rock major and trace element and Nd‒Hf‒Pb isotopes data for granite porphyries from the Keziergayin region in the Kelan Basin. The granite porphyries intrude in the Kangbutiebao Formation with zircon U‒Pb dating of 394±3 Ma. They have the characteristics of subalkaline and metaluminous to weakly peraluminous and show geochemical affinity with I-type granite. The granite porphyry samples display negative εNd(t) (-1.9 to -1.4), positive εHf(t) (+4.3 to +11.4) values, with Nd–Hf decoupling; low Pb isotope compositions; δ18OV-SMOW (6.38-8.45 ‰) is less than 10 ‰, within the range of O isotopes of medium-basic igneous rocks. These geochemical signatures indicate that the granite porphyries originated from lower crust medium−basic igneous rocks extracted from the lithospheric mantle metasomatized by subducted melt. They are characterized by high SiO2 contents and Rb/Sr ratios; low CaO contents and K/Rb ratios, hinting that they were formed by highly evolved magmas, with fractionation crystallization of feldspar, apatite, garnet, allanite and/or monazite. The granite porphyries possess positive Rb, Th, U, Nd, Zr, Pb and light rare earth elements (LREEs) anomalies with strong negative Ba, Nb, Ta, Sr, P, Ti and Eu anomalies, implying that their formation were related to an island arc. Combined with previous studies, it is suggested that the existence of the Early Devonian arc-basin system associated with subducting slab rollback in the Chinese Altai, which belongs to the Siberian active continental margin system.